(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
DCDC2 is a clinically significant protein causing a number of neurological disorders and, hence, is an important protein for analysis. In this study, multiple tools were employed to identify missense SNPs that are harmful to the protein itself and destabilize the interaction of this protein with tubulin subunits. After analyzing all 378 missense SNPs retrieved from the dbSNP database, thirteen were found to have harmful effects on the protein, which are L20P, R23L, G25W, G25R, D26E, I36N, G60E, P68S, G83R, T174I, L179R, R186G, V208E. Among these, four SNPs- T174I, L179R, R186G, and V208E were suggested to be significantly destabilizing for the interaction of the C-DC domain with microtubule, and three SNPs- L20P, D26E, and G83R for the interaction of N-DC domain with microtubule. Based on the total ΔΔG value, SNP R186G and L20P seem most destabilizing for the interaction of the C-DC and N-DC domains. These SNPs are found to affect the protein negatively by analysis using several computational tools. Genetic association and protein-protein interaction studies focused on these SNPs can reveal new findings about dyslexia or other neurodevelopmental disorders. J. Bangladesh Acad. Sci. 47(2); 181-193: December 2023